Molybdenum doping effects for bismuth vanadate photocatalysts on electrochemical performances using the solution process. (1st January 2020) - Chen, Yu-Shiang; Lin, Lu-Yin; Lin, Hung-Yun
Abstract: Metal-doping is widely used to enhance charge generation and reduce carrier recombination of BiVO4 for catalyzing water oxidation. In this work, different Mo-doping levels are applied to synthesize Mo-doped BiVO4 (MBVO) on conductive glasses. Molybdenum plays multiple roles of dopant, structure-confined mediator, and sources for forming additional semiconductor. The MBVO with lower Mo-doping levels presents bi-layered structure with nanowire overlayer and nanorod underlayer, which can develop facile one-dimensional charge-transfer paths and efficient heterojunction. With preferable design of nanowire and nanorod layers, the high light absorption, small charge-transfer resistance and high carrier density are attained for MBVO with 1% Mo-doping, which shows the highest photocurrent density of 2.5 mA/cm 2 at 1.23 VRHE, smallest onset potential of 0.22 VRHE and highest maximum photoconversion efficiency of 2.20%. This work carefully illustrates the function of molybdenum and firstly constructs the unique bi-layered structure for MBVO to display outstanding photoelectrochemical performance for catalyzing water oxidation. Graphical abstract: Image 1 Highlights: Varied Mo-doping levels are used to make Mo-doped BiVO4 (MBVO) as photocatalysts. Mo acts as dopant, structure-confined mediator, and source of other semiconductor. The MBVO with less Mo-doping shows the nanowire and nanorod bi-layered structure. MBVO (1% Mo) shows photocurrent of 2.5 mA/cm 2 and onset potential of 0.22 VRHE . Due to facile one-dimensional charge-transfer paths and efficient heterojunction.